Novel Electromagnetic Microreactor Design for Ammonia Synthesis - Yahya, Noorhana; Puspitasari, P.; Krzysztof, Koziol; Mohd Zabidi, N. A.; Othman, M. Faqih (2010)
Microreactor design for ammonia synthesis with electromagnetic (EM) induction is reported. The Y-shape reactor with dimension of 50mm by 120mm has 5 mixing channels. This microreactor was designed using 2D AUTOCAD software. It was fabricated using MAZAK milling machine that operates using a numerical control functionality computer which was interfaced with MASTERCAM software. Aluminum metal plate with 2mm thickness was used as the microreactor. It was milled for 30 minutes with 0.5mm width of the channel. After the milling process was done two inlets and one outlet with pipe connectors were assembled. To reduce the leakage, a gasket paper was placed between the two plates. Hydrogen and nitrogen gas were mixed and flowed (1.2 bar) into the inlet with 0.05g manganese basedferrite used as the nano-catalyst. The reaction was done inambient condition. The microreactor was placed in a Helmholtz Coils to induced strong EM field. We used Kejldahl method to calculate the 24.9% ammonia yield.